2016
DOI: 10.1016/j.jconrel.2016.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PEG antibodies in the clinic: Current issues and beyond PEGylation

Abstract: The technique of attaching the polymer polyethylene glycol (PEG), or PEGylation, has brought more than ten protein drugs into market. The surface conjugation of PEG on proteins prolongs their blood circulation time and reduces immunogenicity by increasing their hydrodynamic size and masking surface epitopes. Despite this success, an emerging body of literature highlights the presence of antibodies produced by the immune system that specifically recognize and bind to PEG (anti-PEG Abs), including both pre-exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
378
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(385 citation statements)
references
References 93 publications
(114 reference statements)
4
378
0
3
Order By: Relevance
“…Among these, PEG is the most widely used material to reduce uptake by the mononuclear phagocyte system (MPS) for improving the stealth effect because of its low cost and ease of modification 7-9. However, PEGylated nanoparticles have a potential drawback in diagnostic and therapeutic efficacy due to the production of PEG-specific antibodies 10-13. In addition, PEG coating onto nanoparticles has been reported to mitigate the drug release and target cell interaction, thus compromising the diagnostic and therapeutic goals 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, PEG is the most widely used material to reduce uptake by the mononuclear phagocyte system (MPS) for improving the stealth effect because of its low cost and ease of modification 7-9. However, PEGylated nanoparticles have a potential drawback in diagnostic and therapeutic efficacy due to the production of PEG-specific antibodies 10-13. In addition, PEG coating onto nanoparticles has been reported to mitigate the drug release and target cell interaction, thus compromising the diagnostic and therapeutic goals 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Although PEG remains the most established low-fouling material used for modifying drug carriers, alternative materials and strategies have been explored for the development of particles with enhanced biocompatibility and improved in vivo performance (Table 2). [151] For example, low-fouling capsules can be prepared using poly(N-vinyl pyrrolidone) (PVPON) as the building block via LbL assembly. [14,136b,137] The neutral PVPON is both highly biocompatible and low-fouling.…”
Section: Reducing Protein Adsorptionmentioning
confidence: 99%
“…[154] Zwitterionic poly(carboxybetaine) (PCB)-based nanomaterials, as demonstrated by Yang et al, showed prolonged circulation time after both the first and the second administration, indicating negligible production of polymer-specific Abs, which can be an issue for PEG. [139,151] This indicated that PCB could be an alternative to PEG to resist activation of immune responses as well as rapid clearance from blood circulation. [139] Many other synthetic or biological molecules, including poly[N -(2-hydroxypropyl)-methacrylamide], poly(vinyl alcohol), poly(4-acryloylmorpholine), poly(amino acids), and polysaccharides, have also been explored as alternative choices to PEG to develop stealth drug carriers (Table 2).…”
Section: Reducing Protein Adsorptionmentioning
confidence: 99%
“…43 Within the past decade there has been a push to advance beyond PEGylation, as recent literature has documented anti-PEG antibodies that have a detrimental effect on drug efficacy. 44 A range of PEG-alternatives such as poly(N-vinylpyrrolidone), 45 poly(glycerol), 46 poly(zwitterions), 47 poly(carbonates), 48 poly(oxazolines), 49 and poly(sacharrides), 50 have shown promise, and have been reviewed elsewhere. 51,52 In addition, polyphosphoesters (PPE) represent an important alternative to PEG because of their biocompatibility, biodegradability, similar architecture to biomolecules, and ability to be functionalized.…”
Section: Synthetic Strategies For Producing Peptide-polymer Conjugatesmentioning
confidence: 99%